Implementation Of Time Driven Activity Based Costing In Medical Service Tariff Calculation Strategy - Gravihospito, Khansa Rafi; Wulandari, Putu Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Abstract: This research aims to gain a deeper understanding of the implementation of Time-Driven Activity Based Costing (TDABC) as an alternative method for calculating costs and determining hemodialysis unit rates to help hospitals determine alternative, more accurate tariff calculations by calculating costs per unit using TDABC. This research applies qualitative descriptive approach, involving data collection, data reduction, data presentation, and conclusion drawing. Data are collected through observation, interview and documentation. The research results exhibit that TDABC calculation method can be implemented in the Hemodialysis Unit of the Army Hospital Doctor Soepraoen, which replaces the inaccurate calculation method currently used by hospitals, that is difficult for the management to control service costs, estimate profit margins, control operational efficiency, and measure ROI. As such, TDABC method makes cost calculations become more accurate, and certainly makes it easier for management to conduct cost analysis that provides management information about the components that form costs in the hemodialysis unit. From this information, management can determine a more efficient strategy in controlling costs. Customer Profitability Analysis can be used as a tool to evaluate the rates set by the hospital.